A U-shaped association between depression and vigorous physical activity: A cross-sectional study in a cohort of police officers and staff in England - Rabeea Maqsood; Sarah Buckingham; Karyn Morrissey (Journal of Community Safety and Well-Being, 2021)
Policing has become an increasingly sedentary occupation. At the same time, rates of depression are increasing across the police force. Vigorous physical activity (VPA) has been associated with decreasing rates of depression, yet studies of VPA in policing are limited. This study aimed to explore the prevalence of depression and examine its association with VPA in police officers and staff in England, further stratified by gender. A cross-sectional, secondary data analysis of the Airwave dataset was undertaken. The data were analyzed using descriptive statistics and multivariate logistic regression. Of 28,465 police officers and staff in England, 12% reported having doctor-diagnosed depression and 25% were physically inactive. Relative to being physically inactive, undertaking VPA for either four or seven days was significantly associated with having the lowest odds of reporting depression (OR 0.59, 95% CI: 0.51–0.70, p < 0.001) (OR 0.59, 95% CI: 0.45–0.77, p < 0.001), respectively, suggesting a U-shaped/non-linear relationship. This relationship was also observed in the gender-stratification analysis. While the odds of reporting depression were significantly lower for men than women, VPA was significantly associated with reducing the odds of reporting depression slightly more in women (OR 0.43, 95% CI: 0.27–0.67, p < 0.001) than in men (OR 0.50, 95% CI: 0.33–0.75, p < 0.01), indicating women may be more likely to benefit from VPA than men. Vigorous physical activity may provide a protective effect against depression. To prevent the onset of depression in the target population, policy-makers should consider designing physical activity guidelines for police officers to promote VPA in the target population.